Evaluation of the universal soil loss equation in semi-arid and sub-humid climates of India using stage-dependent C-factor - Sharda, V N; Ali, Shakir (The Indian Journal of Agricultural Sciences, 2008)
An experiment was conducted to evaluate the performance of Universal Soil Loss Equation for predominant cropping systems of semi-arid and sub-humid regions of India. The analysis has revealed that values of soil loss as predicted by Universal Soil Loss Equation were lower than observed values for all crop growth stages in the regions except for the third crop growth stage in the sub-humid region. The variation in observed soil loss values among the 3 crop growth stages was quite pronounced as evident from the high values of the co-efficients of variation (49.55 to 109.89) and skewness (-0.03 to 1.63). Nash Sutcliffe model efficiency (?2) for all values of crop growth stages ranged from -0.25 to -5.64 in both the semi-arid and sub-humid regions though it was relatively better in the semi-arid region compared to sub-humid region. The soil loss prediction by Universal Soil Loss Equation for crop growth stages I and II was better with higher co-efficient of determination (R2) value in the semi-arid region compared with the sub-humid region which registered higher value (0.11) during the IIIrd stage. The Student’s t-test also revealed that differences between observed and predicted values are significant (P = 0.05 probability level) with both slope and intercept values significantly different from unity. The Universal Soil Loss Equation predictions for different crop growth stages are significantly different from the observed values of soil loss. The Universal Soil Loss Equation has the potential of predicting crop growth stage dependent soil loss in both the semi-arid and sub-humid regions with varying degree of accuracy which can facilitate adoption of appropriate conservation strategies to minimize the soil loss during different stages of plant growth.